Effectiveness of discharge education using teach-back method on readmission among heart failure patients: A systematic review and meta-analysis. (February 2023) - Oh, Sunyoung; Choi, Hannah; Oh, Eui Geum; Lee, Ji Yea
Abstract: Objective: This study aims to review and evaluate the effectiveness of discharge education using the teach-back method (TBM) on readmission rates among patients with heart failure (HF). Methods: Searches were conducted in five electronic databases (PubMed, CINAHL, Embase, Cochrane Library, and Web of Science) published until May 2022, followed by a manual search of reference lists. The risk of bias in the studies was assessed using the Cochrane Risk of Bias and Joanna Briggs Institute quasi-experimental critical appraisal tool, and meta-analysis was conducted using Cochrane Review Manager 5. Results: Seven studies were included in the review, and the quality of the studies varied, with two studies scoring low on the overall risk of bias. Meta-analysis was conducted using six studies, demonstrating that discharge education using TBM significantly reduced the overall readmission rates (odds ratio = 0.40, 95% confidence interval 0.17–0.94). Conclusions: TBM is an effective educational strategy for reducing the readmission rate in discharged patients with HF. More rigorously designed studies evaluating the effectiveness of education using TBM in patients with HF are needed. Practice implications: Nurses in clinical settings can use TBM in their discharge education to improve HF patients' understanding of the illness and impact long-term outcomes, such as readmission rates. Highlights: ● Teach-back is a strategy to enhance patients' understanding of the education. ● Use of teach-back in discharge education can reduce patients' readmission rates. ● Nurses can implement teach-back as a strategy to better deliver patient education.